myCAST a study on amateur video on the web and its implications on Philippine mainstream television - Tolentino, Daphne Tatiana, Pesayco
This thesis explores the phenomenon of amateur video on the internet and the production process practiced by amateur videographers. Since the advent of Web 2.0, this virtual community of produsers--all amateur content creators--exhibit the potential to create video that can be considered worthy of mainstream television broadcast. In the Philippines, television networks ABS-CBN 2 and GMA-7 have taken notice of these videos and have used them to augment their programs. Their policies and strategies for appropriating these types of content may have a lasting impact on the direction mainstream television content will take shape in this digital age. Through in-depth interviews with amateur video creators, media executives from ABS-CBN 2 and GMA 7, and a media critic, this study documents video production among amateurs, defines the strategies mainstream television networks use to accommodate web videos in their broadcasts and explores the possibilities of a new model of public participation in the shaping of mainstream television content for the future. This is the first study done on the phenomenon of web video vis-a-vis mainstream, television and may well be the first study to document the convergence movement in the broadcast industry in the country.